Representaciones sociales de la Educación para la Salud: docentes Facultad de Medicina, Universidad de Antioquia (2015)
ABSTRACT: To identify the social representations (sr) of health education (he) of the professors from the School of Medicine of the University of Antioquia in the city of Medellin. Methodology: a qualitative study was conducted focusing on the (sr), where the answer to the question “How do you define he?” given by 93 professors was analyzed. Results: the analysis of the data produced the following sr of he: 1) Medical Education associated with the educator’s job; 2) Education for individuals and communities associated to the professional work done by health professionals; and 3) Appropriation of the knowledge for self-care. Discussion: the sr of the professors about he allowed us to understand: that there is no political intention for social reform in the curriculum; that the model of communication underlying this education is the informational one, although there are instances of the relational model; that an instrumental notion of he exists. Thus, it is necessary to make health practitioners aware of the importance of the relational model of communication.